Eficacia de Sambucus peruviana (sauco) en pacientes con hiperplasia prostática benigna sintomática.: Efficcacy of Sambucus peruviana (sauco) in patients with benign symptomic prostatic hyperplasia. - Bueno Ordoñez, Segundo (2022)
Objetive: To determine the efficacy of Sambucus peruviana (sauco) in patients with symptomatic benign prostatic hyperplasia. Methods: Simple randomized clinical trial type study with 30 patients; the preparation with sauco leaves was administered to the patients, orally, at a dose of 45mg/kg/day, for a period of six months; then the variations in the prostate symptoms score were determined according to the international prostate symptom score (IPSS) and the postvoid residual (PVR) determined by ultrasound. Results: The post-treatment analysis according to the symptomatic variation and the PVR was 87% and 97%, respectively; the statistical difference before and after treatment had a highly significant p value (p <0,001). Conclusion: Sambucus peruviana (sauco) is highly effective in the treatment of patients with symptomatic benign prostatic hyperplasia.